1992
DOI: 10.1002/bjs.1800790208
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors from computed tomography in acute left colonic diverticulitis

Abstract: This prospective study examined factors which may predict a poor outcome (complications and recurrence) after a first attack of diverticulitis which has been successfully managed conservatively. Twenty-four of 107 patients who entered the study had a poor outcome: persistent diverticulitis (nine cases), recurrence (seven cases), colonic stenosis (six cases), residual parasigmoid abscess (one case) and colovesical fistula (one case). Eight of the 18 men aged 50 years or less had a poor outcome compared with 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 15 publications
3
33
1
4
Order By: Relevance
“…Independent of the emergent and urgent cases, indication is usually seen in cases of recurrent attacks which require repeated antibiotic therapy and hospitalization. Follow-up studies of patients with a first clinical attack of diverticulitis showed that approximately 25% have a new episode within 2 years and attacks tend to become more severe with length of diverticular disease [28]. Because of the relatively low perioperative risk and low morbidity and mortality, early resection is recommended to avoid emergency surgery in acute exacerbated situations [3, 10, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Independent of the emergent and urgent cases, indication is usually seen in cases of recurrent attacks which require repeated antibiotic therapy and hospitalization. Follow-up studies of patients with a first clinical attack of diverticulitis showed that approximately 25% have a new episode within 2 years and attacks tend to become more severe with length of diverticular disease [28]. Because of the relatively low perioperative risk and low morbidity and mortality, early resection is recommended to avoid emergency surgery in acute exacerbated situations [3, 10, 12].…”
Section: Discussionmentioning
confidence: 99%
“…To establish which patients are more likely to need surgery, Ambrosetti et al [43] clearly showed that the certain parameters in association with diverticulitis can divide the condition into mild and severe forms. The severe parameters seen on CT scanning are predictors of the likelihood of not being able to treat the patient conservatively.…”
Section: The Decision To Operatementioning
confidence: 99%
“…The time interval claimed necessary to distinguish between the two episodes varies among authors, ranging between 1 [1], 2 [2,3] and 3 months [4]. …”
Section: Definitionmentioning
confidence: 99%